199k views
3 votes
What is the factored from of the polynomial function f(x)=x3-6x2+11x-6

1 Answer

1 vote

Answer:


f(x) =(x-1)(x-2)(x-3)

Explanation:

Given


f(x) = x^3-6x^2+11x-6

Required

The factored form


f(x) = x^3-6x^2+11x-6

Split


f(x) =x^3 -3x^2- 3x^2 +2x +9x -6

Rearrange as:


f(x) = x^3 -3x^2 +2x - 3x^2+9x -6

Factorize


f(x) = x(x^2 - 3x + 2) - 3(x^2 - 3x + 2)

Factor out
x^2 - 3x + 2


f(x) = (x^2 - 3x + 2)(x - 3)

Expand


f(x) = (x^2 - 2x - x + 2)(x - 3)

Factorize


f(x) = (x(x - 2) - 1(x - 2))(x - 3)

Factor out
x - 2


f(x) = (x - 1) (x - 2)(x - 3)

User Umesh Kadam
by
5.7k points